THE EFFECTIVENESS OF GROUP GUIDANCE USING THE COGNITIVE BEHAVIOR THERAPY APPROACH WITH COGNITIVE RESTRUCTURING TECHNIQUES TO INCREASE STUDENT SELF-ESTEEM - Tiara Maiza Dianti; Neviyarni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Success in learning will generate positive self-esteem. Competence and achievement are integral elements of self-esteem and related to self-esteem assessment, at SMAN 4 Sungai Penuh it is still found students who have low academic self-esteem such as being ashamed of their physical condition which is not ideal so they do not dare to present themselves , the lack of student effort in practicing self-ability. Conditions like this are a concern, so efforts are needed to increase student self-esteem by providing group guidance services with cognitive restructuring techniques. Therefore, this study aims to (1) analyze the differences in self-esteem of students in the experimental group before and after attending group guidance services using the CBT approach with cognitive restructuring techniques, (2) analyzing the differences in self-esteem of students in the control group before and after attending group guidance services commonly used by counseling teachers at schools (3) analyzing differences in self-esteem of students in the experimental group who attended group counseling services using the CBT approach with cognitive restructuring techniques with groups controls who attended group guidance services that are usually used by guidance counselors at school. The research method used is a quantitative approach. This type of research is a quasi experiment. The sample of this research is 10 students for the experimental group and 10 students for the control group. Sampling using the Slovin formula and sampling with purposive sampling technique. The data collection technique uses a self-esteem scale, Data were analyzed using the Wilcoxon signed ranks test and the Kolmogorov-Smirnov two independent samples using SPSS version 25.00. The results showed that (1) there was a significant difference in the self-esteem of the experimental group students before and after attending group guidance services using the CBT approach with cognitive restructuring techniques, (2) there was a significant difference in the self-esteem of the control group students before and after attending the service group counseling which is usually used by counseling teachers at school, and (3) there are differences in the self-esteem of students in the experimental group who take part in group guidance services using the CBT approach with cognitive restructuring techniques and the control group who take part in group counseling services which are usually used by counseling teachers in schools, This can be seen in the posttest average score of the experimental group which was higher than the control group's posttest average score. So, group counseling cognitive behavior therapy with cognitive restructuring techniques is effective for increasing student self-esteem.